A new record of the family Isonychiidae (Insecta: Ephemeroptera) from the Western Ghats, India with a description of new species - Vasanth, M.; Selvakumar, C.; Subramanian, K. A.; Babu, R.; Sivaramakrishnan, K. G. (Zootaxa, 2019)
A new species belonging to the subgenus Isonychia, of the genus Isonychia Eaton, 1871, is described based on larvae and imagoes collected from Moyar River, Nilgiri District, Tamil Nadu, India. The imagoes of I. moyarensis n. sp. can be distinguished from other described Oriental species of Isonychia (Isonychia) by the combination of characters: (i) forewing with rusty brown maculae in the costal, subcostal, and median areas; (ii) femur and tibia brown, fore leg pale, apices of tarsal segments brownish; (iii) males with distal angles of penes rounded, without serrations; (iv) second segment of gonostylus uniformly convex; and (v) sterna of tenth abdominal segment in female deeply cleft. Isonychia (Isonychia) moyarensis n. sp. can be distinguished in the larval stage from other known Oriental species by the following combination of characters: (i) abdominal terga II–IX with median dark brown maculae progressively larger with dark brown slanting streaks in lateral margins; (ii) trachea of abdominal gills I–VII unbranched; (iii) posterolateral projections on abdominal segments I–VII blunt and progressively longer than those of segments VIII–IX, sharp and distinct; and (iv) abdominal terga X pale yellow in anterior ⅓, and dark brown in the posterior ⅔. A key to the known larvae of Oriental species of Isonychia is also provided.